The Transversal Effects of Bonded Slow Maxillary Expansion - Sevil Akkaya; Sumru Hızlan Lorenzon (Galenos Yayinevi, 1996)
In this study, Minne-Expander appliances to which posterior bite planes have been added were used in the correction of bilateral cross-bites. The aim of this research was to evaluate transversal effects of bonded slow maxillary expansion treatment method. 12 patients having maxillary bilateral cross-bites caused by basal apical narrowness were selected. Posteroanterior cephalograms and hand-wrist radiographs which were taken at the beginning of treatment, at the end of treatment and at the end of retention period formed the material. At the beginning of treatment, the average chronological age was 12.31 1.26 years. The wings of the Minne-Expander were embedded in the posterior bite-planes which had a thickness of 1 millimeter. The spring of the appliance was compressed once a week. The treatment time varied from 2.00-5.16 months. At the end of active treatment, same appliances were worn for retentive purposes for an additional 3 months. Throughout the research period; the values obtained for the transversal width of the upper first molars, maxillary skeletal width and nasal cavity width demonstrated that the main increase was between the transversal width of the upper-first molars, and that the values decreased gradually when moving in an upward direction. Buccal tipping was found in the maxillary halves and upper first molars.